A study on the digestibility of squid, jellyfish and macrozooplankton by leatherback (Dermochelys coriacea, Linnaeus) hatchlings - K. Ramnick Lal Verma (Universiti Pertanian Malaysia, 2012)
The digestibility of squid, jellyfish and macrozooplankton by leatherback (Dermochelys coriacea, Linnaeus) hatchlings were investigated over a 13 day period. The three foods types were prepared in the form agar discs, with 1% chromic oxide (Cr O) incorporated as an internal marker for the evaluation of digestibility.